(untitled) (Torani Journal of Fisheries and Marine Science, 2022)
Boat lift net is an active fishing gear that operates at night using a lamp whose light functions to attract pelagic fish. The purpose of this study is to determine the difference between the catches of the two boat lift net using collecting lights of different colors, this research was held in Polewali Mandar waters in September-November 2020 by following the operation of catching 2 boat lift units. The results showed that the boat using the green collecting light caught 1876.6 kg more fish than the boat using the red light 1534.4 kg, and boat that use green lights have more variety of fish species than boat that use red lights. The different types of fish in the two units of boat lift net are grouper, kerung-kerung, and shark.